PENGARUH GAME ONLINE TERHADAP PEMEROLEHAN BAHASA ANAK USIA 7-13 TAHUN - Nurul Fauziyah; Nanda Riska Dwi Aprila (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2023)
The study entitled "The Influence of Online Games on Language Acquisition in Children Aged 7-13 Years" was conducted to explain the forms of language acquired by children due to online games and to describe the characteristics of online games that affect language acquisition in children aged 7-13 years. This study used descriptive qualitative method. Data in this study from e-books, books, and journals are used as sources of written data. The main data source is children, especially for children aged 7-13 years. Of course, those we studied were children who liked and were proficient in playing online games, both boys and girls. Data collection techniques using observation techniques, documentation techniques, note-taking techniques, and library techniques. The results of the discussion of this study are forms of language in children aged 7-13, namely with 26 terms of word forms. The morphological processes that are experienced include acronymization, substitution and modification of the blanks that form the types of verbs, nouns, and adjectives. Online games that affect children's language acquisition are Free Fire and Mobile Legends games.